The Place of Legal Custom in the System of Sources of Regulation of Private Relations - BANASEVYCH, Iryna I.; HEINTS, Ruslana M.; LOHVINOVA, Mariya V.; MYRONENKO, Ihor V. (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018, 2019)
The relevance of the work is to fully implement the possibility of the exchange of information and technologies between subjects of law for the formation of a balanced legal system. The novelty of the scientific paper is determined by the fact that legal custom is considered not only as a consequence of the emergence of a certain legal system, but also as an environment that forms additional legal relations, formalizing certain traditionalistic legal relations related to the historical and cultural features of the region. In this paper the authors show the genesis of the legal custom, its forms of implementation and the principles of its implementation, which can be applied to case law and codified systems of law. The scientific paper reveals the concept of tradition and custom; legal custom is differentiated from the case and the possibility of its evolution is shown. The practical application of the research determines the possibility of forming an innovative legal environment, along with the development of traditional legal systems.